Pengaruh Keberadaan Program Lumbung Pangan terhadap Tingkat Pendapatan Petani Padi Lokal di Desa Danau Karya Kecamatan Anjir Pasar Kabupaten Barito Kuala - Erafando lrawan Margiyanto; Luki Anjardiani; Hairi Firmansyah (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
The· purposes of the study were to find out the effect of Lumbung Pangan (Food Barn) Programme to rice farmer's income whether members or non members of the food barn, and to describe the problems faced by the farmers to the existence of the food barn in Danau Karya Village of Anjir Pasar District of Barito Kuala Regency. The results of the study showed that the total cost per hectare expended by the farmers who were members of the food barn was greater than the total cost per hectare spent by non-member farmers, with a difference of Rp 432,228.85The rice farming revenue earned by the member farmers was higher than that gained by non-member farmers, with a margin of Rp 786, 690. 64 per hectare. Moreover, the income received by the member farmers was higher than the income gained by non-member farmers, with a margin of Rp 992, 143.97 per hectare. The results of the calculation using the t test, scored thit(1,823). Figures from the t table with significance level a= 5% or 0.05 with free progression or degree of freedom (df) of 39 was 1.645. It can be concluded that Food Barn Program in Danau Karya Village of Anjir Pasar District affected the increase in the income of respondent farmers who were the members of food bam. The problems or constraints that the member farmers faced was that there were some member farmers whose houses were far enough to reach the barn, insufficient capacity of the barn, and greater costs for transporting fertilizer. Meanwhile, the problems that non-member farmers had were that the use of the barn in the village was only for the registered member farmers, causing social jealousy between the non-member farmers and the member farmers who used the barn.